How to be a witch - Balkan, Gabrielle; Gozansky, Shana (Rise x Penguin Workshop, an imprint of Penguin Random House LLC, 2024)
"Most people, kids included, have very specific associations with "witch" -- perhaps a scheming, warted, and/or green-faced woman in a pointy hat and heels, brewing a potion with gruesome ingredients intended for harm or dark magic. And though witches are real, none of that is actually true! Over many centuries, knowledgeable, powerful, and healing women have been demonized by men who fear a loss of power or pride. And through those same centuries, certain people have passed down their lived and learned knowledge of nature's power to heal. Those who identify as witches today are most often natural healers whose wisdom serves to help those around them. Written in a conversational, engaging tone, and illustrated in an accessible and appealing style, this book dispels stereotypes and expands young readers' knowledge of what it means to be a REAL witch. Complete with a suggested potion and spell in the backmatter, this is a current and worthy celebration of witches!"--